Microinjection of histamine into the cerebellar vermis impairs emotional memory consolidation in mice - Gianlorenco, A. C. L.; Canto-de-Souza, A. [UNESP]; Mattioli, R. (Pergamon-Elsevier B.V. Ltd, 2011)
The biogenic amine histamine is an important neurotransmitter in the central nervous system that has been implicated in learning and memory processes. Experimental evidence indicates that the role of the cerebellum may be more complex than the simple regulation of motor responses, and recent studies have demonstrated significant involvement of the cerebellum in emotional memory consolidation. This study investigated the effect of histamine microinjected into the cerebellar vermis on emotional memory consolidation in mice in the elevated plus-maze (EPM). The cerebellar vermis of male mice (Swiss Albino) were implanted with guide cannulae. The mice weighed between 25 and 30g. After three days of recovery, behavioral tests in the EPM were performed on two consecutive days: the testing periods were called. Trial 1 and Trial 2. Immediately after Trial 1, the animals received microinjections of histamine in the cerebellar vermis (0.54, 1.36, 2.72, and 4.07 nmol/0.1 mu l). on both days, the test sessions were recorded to enable analysis of behavioral measures. The decrease in open arm exploration (% entries and % time spent in the open arms) in Trial 2 relative to Trial 1 was used as a measure of learning and memory. The data were analyzed using One-way Analysis of Variance (ANOVA) and Duncan's tests. The percentage of open arm entries (%OAE) and the percentage of time spent in the open arms (%OAT) were reduced in Trial 2 relative to Trial 1 for the control group; the same was true for the group that was microinjected with histamine at doses of 0.54 (%OAE and %OAT) and 1.36 nmol (%OAT). However, when the animals received histamine at doses of 2.72 and 4.07 nmol, their open arm exploration did not decrease. No significant changes were observed in the number of enclosed arm entries (EAE), an EPM index of general exploratory activity. These results suggest that there is a dose-dependent inhibitory effect of histamine microinjected into the cerebellar vermis on emotional memory consolidation. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Histamine; Cerebellar vermis; Emotional memory; Elevated plus-maze; Mice